Design and test technology for dependable systems-on-chip - Ubar, Raimund, 1941-; Raik, Jaan, 1972-; Vierhaus, Heinrich Theodor, 1951- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
Covers aspects of system design and efficient modelling, and also introduces various fault models and fault mechanisms associated with digital circuits integrated into System on Chip (SoC), Multi-Processor System-on Chip (MPSoC) or Network on Chip (NoC).
Keywords: Systems on a chip -- Design and construction.; Networks on a chip -- Design and construction.; Systems on a chip -- Testing.; Networks on a chip -- Testing.; elektronické knihy; electronic books